Neurobiological Studies of Addiction in Chronic Pain States - Fairbanks, Carolyn A.; Martin, Ph.D., Thomas J. (Contemporary Clinical Neuroscience, 2014)
Using rodent models, the contributors explore the basic neurobiology of the relationship among chronic pain, opioid pharmacology, and addiction. Combining various pain models with opioid self-administration and central administration pharmacotherapies allows researchers to answer important questions about: 1. The efficacy of opioid treatment under conditions of chronic pain of different etiology. 2. Alterations in the efficacy of opioid treatment under conditions of long-term opioid pharmacotherapy. 3. The potential for conversion or escalation of extra-analgesic motivation for opioid use beyond that required for pain relief. 4. The possibility of addiction development in chronic pain sufferers. Merging the field of pain researchers with that of addiction research has presented some unique challenges and this volume seeks to provide some guidance for future study design in addition to a summary of current findings in the area.